PENGARUH PENERAPAN MODEL ADI TERHADAP KETERAMPILAN BERPIKIR KRITIS BERDASARKAN PERBEDAAN TIPE KEPRIBADIAN - Fadila Nurhusna; Undang Rosidin; Kartini Herlina; Neni Hasnunidah (Unika Santu Paulus Ruteng, 2018)
This study aims to determine the effect of the application of the ADI model on critical thinking skills based on different types of choleric personality, melancholy, phlegmatic, and sanguine. This study uses a quasi-experimental type Pretest-posttest Control Group Design. The results showed that there was a significant effect of learning with the ADI model on critical thinking skills in the type of choleric personality, melancholy, phlegmatic, and sanguine and there were differences in critical thinking skills between the four personality types, namely choleric and melancholy, phlegmatic, sanguine, this is because choleric students who are more likely to appear more active in communicating and moving quickly to act, wherein this ADI model are required to give a lot of argumentation through verbal or communicating between fellow students to give their arguments. This shows that the use of the ADI learning model is able to improve students' critical thinking skills.